Evaluasi Efektivitas Program Bank Sampah dalam Mengurangi Timbulan Sampah dan Emisi Metana di Kawasan Perkotaan - Erna Tri Asmorowati; Eko Sutrisno; Diah Sarasanty; Ainin Bashiroh; Faizatus Sholikhah (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Urban waste generation continues to rise in line with increased consumption patterns, particularly in rapidly developing cities. This study analyzes the effectiveness of community-based waste banks in reducing municipal waste volume, lowering methane emissions, and strengthening urban climate resilience. Waste banks play a pivotal role in diverting recyclable and organic materials from landfills through structured sorting systems, economic incentives, and integrated organic processing such as composting and maggot cultivation. These mechanisms significantly reduce anaerobic decomposition, which is the primary source of methane emissions in landfills. Community participation, institutional capacity, technological support, and government collaboration emerge as key factors that determine the overall performance of waste bank programs. The development of circular economy practices within waste bank operations contributes to environmental quality improvement while simultaneously generating economic benefits for local communities. The findings highlight that waste banks are not only tools for waste reduction but also essential components of urban climate mitigation strategies. Their ability to integrate social, ecological, and economic functions positions them as effective, low-cost solutions for modern urban environmental management.